Comparison of myo-inositol and metformin on mental health parameters and biomarkers of oxidative stress in women with polycystic ovary syndrome: a randomized, double-blind, placebo-controlled trial. (2nd October 2018) - Jamilian, Hamidreza; Jamilian, Mehri; Foroozanfard, Fatemeh; Afshar Ebrahimi, Faraneh; Bahmani, Fereshteh; Asemi, Zatollah
Abstract: Introduction: Data on comparison of myo-inositol and metformin on mental health parameters and biomarkers of oxidative stress in subjects with polycystic ovary syndrome (PCOS) are scarce. This purpose of this study was to compare of myo-inositol and metformin on mental health parameters and biomarkers of oxidative stress in subjects with PCOS. Methods: This randomized controlled trial was conducted among 60 subjects diagnosed with PCOS according to the Rotterdam criteria. Subjects were randomly assigned into two groups to intake either myo-inositol ( n  = 30) or metformin ( n  = 30) for 12 weeks. Parameters of mental health were recorded at baseline and after the 12-week intervention. Fasting blood samples were obtained at baseline and the end of the study to determine biomarkers of biomarkers of oxidative stress. Results: After the 12-week intervention, changes in beck depression inventory total score (−1.0 ± 1.7 vs. −0.3 ± 0.7, p  = 0.03), general health questionnaire scores (−1.7 ± 2.9 vs. −0.5 ± 1.2, p  = 0.02), depression anxiety and stress scale scores (−3.9 ± 6.4 vs. −0.9 ± 1.9, p  = 0.01) and plasma total antioxidant capacity (TAC) concentrations (+106.1 ± 69.6 vs. +2.1 ± 132.4 mmol/L, p  < 0.001) in the myo-inositol group were significantly different from the changes in these indicators in the metformin group. Myo-inositol supplementation for 12 weeks among patients with PCOS did not affect plasma glutathione and malondialdehyde levels. Conclusions: Overall, our data supported that myo-inositol supplementation for 12 weeks among patients with PCOS had favorable effects on parameters of mental health and plasma TAC levels.